ANALISIS ENERGI KINETIK MAKSIMUM JATUHAN BATUAN (ROCK FALL) DALAM PENERAPAN TEKNOLOGI ROCK FENCE - Ihwan Fauzi; Hisyam Gusman Sugarda; Syafril Ramadhon (Direktorat Bina Teknik Jalan dan Jembatan, 2022)
Rock fall is a very fast bedrock movement where material is released from a steep slope and moves by falling, bouncing, rolling or sliding. West Java Province has a frequency of 1129 landslides throughout 2020 which underlies the need for a study of locations that have the potential for rock fall and simulation calculations to determine the type of rock fall barrier that can be used at that location. Rock fence as a passive slope protection method as one of the rock fall countermeasures. The analysis is carried out using software to determine the most appropriate type of rock fence method. Based on the analysis, the maximum kinetic energy at Location 1, Location 2 and Location 3 was 1,630.68 kJ, 1,209.11 kJ and 397.82 kJ, respectively. Thus, the countermeasure for Location 1 can use a Category 4 rock fence with the maximum energy level value being in the range of 1500 kJ MEL < 2000 kJ, while countermeasures for Locations 2 and 3 can use Category 3 and Category 1 rock fences respectively. Further collection of slope geometry data and historical rock fall data is needed to be able to simulate various rock fall conditions, rock reflection heights and rock maximum kinetic energy so as to sharpen the analysis results. Keywords: rock fence, rock fall classification, kinetic energy, slope protection, simulation